Attitudes and norms about intimate partner violence: What makes women more impressionable? - Gaurav Dhamija; Mehreen Mookerjee; Manini Ojha; Sanket Roy (Global Labor Organization (GLO), 2024)
We evaluate the causal impact of average neighbourhood attitudes justifying intimate partner violence (IPV) on own attitudes using nationally representative data from the fifth wave of the National Family Health Survey of India. To address endogeneity concerns in estimating peer in uences, we utilize exogenous variation in the average exposure of neighbourhood women to their parental IPV in a leave-one-out instrumental variable strategy. We find robust evidence that a 1 sd increase in a woman's average neighbourhood attitudes justifying IPV leads to a 0.36 sd increase in her attitudes justifying the same. We establish the importance of peer in uences on a woman's acceptability of IPV as justifi- able, especially among less educated, unemployed, having no assets or media exposure and bearing more daughters than sons, making them more impressionable. This underscores the need for enhanced implementation of policies targeting women's empowerment to arrest the perpetration of gender-biased social norms.
Keywords: C26; J12; J16; O12; 330; Neighbourhood; Domestic Violence; Social Effects; Attitudes; Instrumental Variable; India